Love at first swipe (right) an analysis of how Tinder mediates romantic relationships between strangers - Ledesma, Stephanie B. 1996-
"This study analyzes how romantic connections are mediated and constructed by Tinder - a mobile dating application. It enables strangers to initiate interaction online through its swipe left and right, and messaging function. Given the number of Tinder users in the Philippines, the researcher delves into how these online daters build romantic connections through it. Online dater's activities were examines using an interpretive approach. This qualitative study was guided by a theory and model on online interpersonal relationships proposed by Joseph Walther. Social Information Processing Theory (Walther, 1992) was used to examine user activities by looking at self-presentation, impression management, and development of relationship. The progress of each connection was then analyzed using Walther's Hyperpersonal Model of Communication (1996), wherein relations from impersonal to hyperpersonal phase were examined. The results showed that users try to be as honest as possible in presenting themselves online. They also utilize other functions on Tinder such as Spotify and Instagram in getting to know the other person. As their relationship progress, they use their platforms. This shows that Tinder does not support formation of deeper relationship and is only a platform used by online daters to new meet people."